The Epistemological Evolution of the Integration of Knowledge: From al-Faruqi’s Islamization of Knowledge towards Amin Abdullah’s Interconnection and Kuntowijoyo’s Prophetic Social Science - Eko Ngabdul Shodikin; Miftahuddin; Mansur (Yayasan Azhar Amanaa Yogyakarta, 2026)
The challenges of modernity and the complexity of social crises demand a repositioning of Islamic education so that it does not become trapped in the dichotomy of secular and normative sciences. To address this need, this study aims to examine and synthesize the epistemological evolution of the discourse on the integration of knowledge through a comparative analysis of the thoughts of Ismail Raji al-Faruqi, M. Amin Abdullah, and Kuntowijoyo. Employing a qualitative approach with a library research design and content analysis techniques, this study dissects the fundamental structures of the primary literature of these three figures to trace their ontological, epistemological, and axiological frameworks. The results of the study indicate a linear and complementary paradigm shift. This evolution was initiated by methodological purification efforts through al-Faruqi's Islamization of Knowledge, then progressed toward an open interdisciplinary dialogue through Amin Abdullah's Integration-Interconnection paradigm, and culminated in practical field transformation through Kuntowijoyo's Prophetic Social Sciences. The conclusion of this study confirms that these three concepts do not negate one another, but rather form a complete continuum of the